Contribution of IL-17 in Steroid Hyporesponsiveness in Obese Asthmatics Through Dysregulation of Glucocorticoid Receptors α and β - Al Heialy, Saba; Gaudet, Mellissa; Ramakrishnan, Rakhee K.; Mogas, Andrea; Salameh, Laila; Mahboub, Bassam; Hamid, Qutayba (Frontiers in Immunology, 2020)
Obesity is on the rise worldwide and is one of the most common comorbidities of asthma. The chronic inflammation seen in obesity is believed to contribute to this process. Asthma and obesity are associated with a poorer prognosis, more frequent exacerbations and poor asthma control to standard controller medication. Difficult-to-treat asthma is associated with increased levels of Th17 cytokines which have been shown to play a central role in the upregulation of glucocorticoid receptor-beta (GR-β), a dominant-negative inhibitor of the classical GR-α. In this study, we studied the role of IL-17 cytokines in steroid hyporesponsiveness in obese asthmatics. We stimulated lean and obese adipocytes with IL-17A and IL-17F. Adipocytes obtained from obese patients cultured in vitro in the presence of IL-17A for 48 hours showed a decrease in GRα/GRβ ratio as compared to adipocytes from lean subjects where GR-α/GR-β ratio was increased following IL-17A and IL-17F stimulation. At protein level, GR-β was increased in obese adipocytes with IL-17A and IL-17F stimulation. IL-8 and IL-6 expression was increased in IL-17-stimulated obese adipocytes. Pre-incubation with Dexamethasone (Dexa) led to a decrease in GR-α/GR-β ratio in obese adipocytes which was further affected by IL-17A whereas Dexa led to an increase in GR-α/GR-β ratio in lean adipocytes which was decreased in response to IL-17A. TGF-β mRNA expression was decreased in obese adipocytes in response to Th17 cytokines. We next sought to validate these findings in obese asthmatic patients. Serum was collected and GR-α, GR-β, IL-17A, IL-17F and IL-13 protein expression was assessed by ELISA. Serum obtained from obese asthmatic subjects showed a decrease in GRα/GRβ protein expression with an increase in IL-17F and IL-13 as compared to serum obtained from non-obese asthmatics. In conclusion, steroid hyporesponsiveness in obese asthmatic patients can be attributed to Th17 cytokines which are responsible forin the dysregulation of the GRα/GRβ ratio and the inflammatory response.